A Novel BODIPY Quaternary Ammonium Salt-Based Fluorescent Probe: Synthesis, Physical Properties, and Live-Cell Imaging - Deng, Peng; Xiao, Fuyan; Wang, Zhou; Jin, Guofan (Frontiers in Chemistry, 2021)
The development of biological fluorescent probes is of great significance to the field of cancer bio-imaging. However, most current probes within the bulky hydrophobic group have limited application in aqueous medium and restricted imaging under physiological conditions. Herein, we proposed two efficient molecules to study their physical properties and imaging work, and the absorption and fluorescence intensity were collected with varying ions attending in aqueous medium. We enhance the water solubility through the quaternization reaction and form a balance between hydrophilic and hydrophobicity with dipyrrome-theneboron difluoride (BODIPY) fluorophore. We introduced pyridine and dimethylaminopyridine (DMAP) by quaternization and connected the BODIPY fluorophore by ethylenediamine. The final synthesized probes have achieved ideal affinity with HeLa cells (human cervical carcinoma cell line) in live-cell imaging which could be observed by Confocal Microscope. The probes also have a good affinity with subcutaneous tumor cells in mice in in vivo imaging, which may make them candidates as oncology imaging probes.